2019
DOI: 10.3390/d11010005
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Control of Invasive Freshwater Crayfish: From Traditional to Innovative Methods

Abstract: Invasive alien species are widespread in freshwater systems compared to terrestrial ecosystems. Among crustaceans, crayfish in particular have been widely introduced and are considered a major threat to freshwater ecosystem functioning. New emerging techniques for detecting and controlling invasive crayfish and protecting endangered native species are; thus, now highly desirable and several are under evaluation. Important innovations have been developed in recent years for detection of both invasive and native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 128 publications
1
41
0
1
Order By: Relevance
“…Even though various control methods have been attempted to control nuisance crayfish, crayfish eradication is almost impossible except in limited circumstances (Gherardi, Aquiloni, Diéguez-Uribeondo, & Tricarico, 2011;Hansen, Ives, Vander Zanden, & Carpenter, 2013;Holdich, Gydemo, & Rogers, 1999;Manfrin, Souty-Grosset, Anastácio, Reynolds, & Giulianini, 2019). However, Hansen et al (2013) pointed out that more frequently droughts in the future may facilitate eradication of invasive rusty crayfish (Orconectes rusticus) in Wisconsin lakes.…”
Section: Management Implicationsmentioning
confidence: 99%
“…Even though various control methods have been attempted to control nuisance crayfish, crayfish eradication is almost impossible except in limited circumstances (Gherardi, Aquiloni, Diéguez-Uribeondo, & Tricarico, 2011;Hansen, Ives, Vander Zanden, & Carpenter, 2013;Holdich, Gydemo, & Rogers, 1999;Manfrin, Souty-Grosset, Anastácio, Reynolds, & Giulianini, 2019). However, Hansen et al (2013) pointed out that more frequently droughts in the future may facilitate eradication of invasive rusty crayfish (Orconectes rusticus) in Wisconsin lakes.…”
Section: Management Implicationsmentioning
confidence: 99%
“…It should be noted that four species from the set, C. patzcuarensis and all three Procambarus species, can serve as vectors of crayfish plague (Keller, Pfeiffer, Roessink, Schulz, & Schrimpf, 2014;Mrugała et al, 2015), and this threat is becoming more realistic after the finding of the pathogen and its host P. clarkii in Indonesia (Putra et al, 2018). Prevention of NICS arrival is essential, because studies have shown that their later elimination is extremely difficult and at best very costly (Manfrin et al, 2019;Nunes, Hoffman, Zengeya, Measey, & Weyl, 2017;Peay et al, 2019;Peay, Dunn, Kunin, McKimm, & Harrod, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Endemic crayfish are threatened by invasive species through direct competition, habitat alteration and loss, modification of the structure of freshwater food webs, and by disease transmission (Gherardi, 2007). Mitigation or eradication of established nonindigenous crayfish species (NICS) is mostly impossible, and no strategy is widely effective in this regard (Gherardi, Aquiloni, Diéguez-Uribeondo, & Tricarico, 2011;Manfrin, Souty-Grosset, Anastácio, Reynolds, & Giulianini, 2019). Recently, a new threat to Cherax crayfish was found in Java, Indonesia: the crayfish plague pathogen Aphanomyces astaci (Putra et al, 2018).…”
mentioning
confidence: 99%
“…On the other hand, biological control represented by introduction of natural predators may be potentially dangerous to native crayfish as well as to amphibians. According to current knowledge on eradication actions, biotechnological methods such as Sterile Male Release Technique might be an effective temporary way for invasive crayfish management, as they are safe to environment and already tested mainly on P. clarkii (Manfrin et al, 2019;Sandodden, 2019). Environmentally safe methods allowing ultimate eradication of invasive crayfish are urgently needed.…”
Section: Discussionmentioning
confidence: 99%